Clinical - Pathological aspects of hepatocellular carcinoma in cattle - Mendonça, Ana Paula Abreu [UNESP]; Costa, Joselito Nunes; Biscarde, Carmo Emanuel Almeida; da Anunciação Pimentel, Luciano; de Oliveira Filho, José Carlos (Universidade Federal do Rio Grande do Sul, 2019)
Background: The hepatocellular carcinoma (HCC) is a malignant neoplasm of hepatocytes of rare occurrence in farm animals, with ruminants being the most affected species. This neoplasm is characterized by nonspecific symptoms and it is etiology in animals has not yet been fully elucidated, although aflatoxin has been shown to be a risk factor in the development this neoplasia. Since hepatic tumors in cattle are commonly incidental findings found in postmortem examination, the objective of this paper is to describe the clinical, laboratory and pathological findings in a cow with this neoplasm. Case: A 5-year-old, adult, Girolando cow weighing 350 kg was referred to the Veterinary Hospital of the Federal University of Recôncavo da Bahia, Brazil, with a history of decreased appetite and weakness for one month. The animal was raised in a semi-intensive system, with a corn-based diet, and regular vaccination. Futhermore, was not treated at the farm of origin and three days before being admitted to the hospital, began to present edema of the dewlap. On examination at our center, the cow was in lean, active, with mucupurulent secretion in nostrils; ocular conjunctiva edema; and edema of the dewlap. The cow had neutrophilia, hypofibrinogemia, hypoproteinemia, and trombocytopenia. It also had tachycardia, tense abdomen, engorgement of the vessels of the face and jugular veins, stasis test and bilaterally positive jugular pulse. Although evidence of pain in reticulum was negative in the examination, the initial diagnostic suspicion established was of traumatic reticular pericarditis. The therapeutic protocol instituted was daily monitoring, flunixin meglumine and flofernicol. The examination of rectal palpation revealed in the right flank an irregular-sized parenchymal structure with enlarged and palpacion in pain. Thus, by location and texture, it was suspected that the structure in question was a liver or kidney. However, the dosage of creatinine ruled out renal damage, and persistent hypoproteinemia reinforced the suspicion of hepatic impairment. In view the deterioration of the clinical condition and the suspicion of hepatic impairment, such as hepatic insufficiency, hepatitis or hepatic abscess, we opted for a right exploratory laparotomy. The surgery confirmed the presence of various granulomas throughout the liver, a non-luster organ, bulging edges with erosions and deposition of fibrin on the surface, confirming liver dysfunction. However, the animal died during the surgical procedure, and necropsy was performed, evidencing a focally extensive mass and multiple nodules of various sizes in the liver, lymph nodes and lung. In the microscopy of these nodules, cells similar to hepatocytes were observed, arranged in the form of strands or in agglomerates. Thus, similar to the reports in the literature, the diagnosis of HCC was carried out postmortem by necropsy and histopathology. Discussion: The diagnosis of HCC was based on clinical, laboratory and anatomopathological findings. The hypoproteinemia and persistent hypofibrinogenemia suggest a hepatic dysfunction that was confirmed on surgery and histopathology. Primary liver tumors, although rare in production animals, must be considered in the differential diagnosis of weight loss, weakness and edema in cattle. It was not possible to determine the etiology of the neoplasia in this case, however, the possibility of aflatoxicosis by corn should not be ruled out as a probable inducer, since corn was a constituent of the diet provided to the animal.
Keywords: Cow; Farm animals; HCC; Hepatic neoplasm; Hepatopathy